Innovative security solutions for information technology and communications : 10th International Conference, SecITC 2017, Bucharest, Romania, June 8-9, 2017, Revised selected papers /: 10th International Conference, SecITC 2017, Bucharest, Romania, June 8-9, 2017, Revised selected papers. (2017) - Unknown
No abstract available